Public Trust in Thailand’s Government by Using Artificial Intelligence in Government Services - Surapraseart, Korakot; Phuengpha , Noppawan (Procedia of Social Sciences and Humanities, 2024)
As Thailand advances in its digital transformation journey, Artificial Intelligence (AI) is increasingly being integrated into public services to enhance efficiency, transparency, and citizen satisfaction. This study explores how AI technologies have been deployed in government services, focusing on Thailand’s Yala Smart City project as a case study. The research investigates the benefits of AI in public governance, including improved service delivery, reduced corruption, and the enhancement of public trust. Using a quantitative approach, data from public surveys, service usage statistics, and policy effectiveness reports were analyzed to assess the public’s trust in AI-powered government services. Key findings indicate that AI implementation in public services, particularly in Yala, has improved accessibility, transparency, and efficiency, contributing to increased trust in the government. However, concerns about data privacy, ethical use of AI, and the digital divide remain prevalent. This paper also discusses the importance of regulatory frameworks, data privacy safeguards, and mechanisms for accountability to ensure the ethical deployment of AI. Recommendations are provided for improving public trust through responsible AI governance and continuous stakeholder engagement, emphasizing the role of inclusivity and transparency in the digital era. The lessons from Yala’s Smart City initiative offer valuable insights for other regions aiming to adopt AI in their government services.